Mus musculus papillomavirus 1 is a key driver of skin cancer development upon immunosuppression. Issue 2 (3rd November 2020) - Dorfer, Sonja; Strasser, Katharina; Schröckenfuchs, Georg; Bonelli, Michael; Bauer, Wolfgang; Kittler, Harald; Cataisson, Christophe; Fischer, Michael B.; Lichtenberger, Beate M.; Handisurya, Alessandra
Abstract : Epidemiological and experimental data implicate cutaneous human papillomavirus infection as co‐factor in the development of cutaneous squamous cell carcinomas (cSCCs), particularly in immunocompromised organ transplant recipients (OTRs). Herein, we established and characterized a skin cancer model, in which Mus musculus papillomavirus 1 (MmuPV1) infection caused cSCCs in cyclosporine A (CsA)‐treated mice, even in the absence of UV light. Development of cSCCs and their precursors were observed in 70% of MmuPV1‐infected, CsA‐treated mice on back as well as on tail skin. Immunosuppression by systemic CsA, but not UV‐B irradiation, was a prerequisite, as immunocompetent or UV‐B–irradiated mice did not develop skin malignancies after infection. In the virus‐driven cSCCs the MmuPV1‐E6/E7 oncogenes were abundantly expressed, and transcriptional activity and productive infection demonstrated. MmuPV1 infection induced the expression of phosphorylated H2AX, but not degradation of proapoptotic BAK in the cSCCs. Transfer of primary cells, established from a MmuPV1‐induced cSCC from back skin, into athymic nude mice gave rise to secondary cSCCs, which lacked viral DNA, demonstrating that maintenance of the malignant phenotype was virus independent. This papillomavirus‐induced skin cancer model opens future investigations into viral involvement, pathogenesis, and cancer surveillance, aiming at understanding and controlling the high incidence of skin cancer in OTRs. Abstract : This murine model demonstrates the synergy of Mus musculus papillomavirus 1 skin infection and systemic immunosuppression in the development of cutaneous squamous cell carcinomas, even in the absence of UV‐B light.